First demonstration of phosphate enhanced atomically dispersed bimetallic FeCu catalysts as Pt-free cathodes for high temperature phosphoric acid doped polybenzimidazole fuel cells - Cheng, Yi; Wang, M.; Lu, S.; Tang, C.; Wu, X.; Veder, Jean-Pierre; Johannessen, B.; Thomsen, L.; Zhang, J.; Yang, S.Z.; Wang, S.; Jiang, San Ping (ELSEVIER, 2021)
Phosphate poisoning of Pt electrocatalysts is one of the major barriers that constrains the performance of phosphoric acid-doped polybenzimidazole (PA/PBI) membrane fuel cells. Herein, we developed new atomically dispersed bimetallic FeCu coordinated with nitrogen-doped carbon nanotubes (FeCu/N-CNTs) as Pt-free oxygen reduction reaction (ORR) electrocatalysts. The cell with FeCu/N-CNTs cathodes delivers a peak power density of 302 mWcm−2 at 230℃, similar to that using Pt/C electrocatalysts (1 mgPt cm−2) but with a much better stability. In contrast to phosphate poisoning of Pt/C, FeCu/N-CNTs show PA enhanced activities. DFT calcualtions indicate that phosphate promotion effect results from the stronger binding of phosphate on Cu sites, which decreases the activation energy barrier for the cleavage of the O2 double bond and provides local protons to facilitate the proton-coupled electron transfer ORR. The results also show that FeCu/N-CNTs have a much better activity for ORR as comapre to Fe single atom catalysts coordinated with nitrogen-doped carbon nanotubes, Fe/N-CNTs. This study demonstrates the promising potential of bimetallic FeCu/N-CNTs as true Pt-free, highly active and durable cathodes for PA/PBI based high temperature polymer electrolyte fuel cells.